2019
DOI: 10.3390/geosciences9040191
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trapped Air on the Tsunami-Induced Transient Loads and Response of Coastal Bridges

Abstract: In response to the extensive damage of coastal bridges sustained in recent tsunamis, this paper describes an investigation into tsunami-induced effects on two common bridge types, an open-girder deck with cross-frames and one with solid diaphragms. To this end, large-scale (1:5) physical models with realistic structural members and elastomeric bearings were constructed and tested under a range of unbroken solitary waves and more realistic tsunami-like transient bores. The flexible bearings allowed the superstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Other critical aspects related to the hydrodynamic effects on coastal structures that have been identified by previous studies include the high aleatory variability of bore impact on structures [13,17], the importance of structural flexibility and dynamic fluid-structure interaction [17,23,24], the critical role of trapped air below elevated decks [21,[25][26][27][28] and the demand on individual connections and columns [29]. For example, Robertson et al [13] found a significant variability in the impulsive uplift pressures applied by a turbulent bore on the slab soffit of a vertical wall with an overhang, with the maximum pressures at selected locations ranging between 3 and 7.5 kPa among the different repetitions of the same bore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other critical aspects related to the hydrodynamic effects on coastal structures that have been identified by previous studies include the high aleatory variability of bore impact on structures [13,17], the importance of structural flexibility and dynamic fluid-structure interaction [17,23,24], the critical role of trapped air below elevated decks [21,[25][26][27][28] and the demand on individual connections and columns [29]. For example, Robertson et al [13] found a significant variability in the impulsive uplift pressures applied by a turbulent bore on the slab soffit of a vertical wall with an overhang, with the maximum pressures at selected locations ranging between 3 and 7.5 kPa among the different repetitions of the same bore.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies found that the air entrapment below elevated decks with girders can significantly increase the maximum total uplift forces generated by solitary waves [21,30]. However, the trapped air can also increase the overturning moment, while it has a complex and inconsistent effect on the total slamming and on the uplift demand in the offshore bearings and columns generated by bores [28].…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach of using multiple load cases in the design of coastal decks subjected to storms has also been used in AASHTO [25]. An alternative method for calculating the design values for individual elastomeric bearings that connect the deck to the substructure, is to use non-dimensional design curves, as the ones provided in [26]. It is noteworthy that in addition to wave loads on decks and connections, more recently some studies have investigated the hydrodynamic loads on columns, bridge piers and pile caps [27][28][29], while others have focused on the resilience assessment of coastal bridges [30] and drag-induced displacements of bridge spans exposed to hurricanes [31].…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach of using multiple load cases in the design of coastal decks subjected to storms has also been used in AASHTO [25]. An alternative method for calculating the design values for individual elastomeric bearings that connect the deck to the substructure, is to use non-dimensional design curves, as the ones provided in [26]. It is noteworthy that in addition to wave loads on decks and connections, more recently some studies have investigated the hydrodynamic loads on columns, bridge piers and pile caps [27][28][29], while others have focused on the resilience assessment of coastal bridges [30] and drag-induced displacements of bridge spans exposed to hurricanes [31].…”
Section: Introductionmentioning
confidence: 99%